The Impact of Leverage and Liquidity on Firm Profitability - Nurriqli, Arifia; Utiarahman, Nurnaningsih; Hendrawan, Henky; Durya, Ngurah Pandji Mertha Agung; Alfiana, Alfiana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
This study aims to find empirical evidence of the influence of leverage (DER) and liquidity (CR) on profitability (ROA). In this research, researchers employed quantitative method using panel data regression. The study population consists of the companies listed on the Jakarta Islamic Index (JII 30) 2020-2024, and the purposive sampling technique is used to determine the sample size. A total of 105 samples from 21 companies were selected for this study. The data analysis techniques use EViews 12. Based on the study findings, profitability (ROA) significantly affected by debt to equity ratio (DER) and current ratio (CR). This study can serve as a guide for businesses looking to boost and enhance performance as well as for investors assessing company performance to gain investment certainty. The practical implication of these findings is the management stoct issuers could maintain the company good performance in order to increase investor trust in a sustainable manner.